Gold-catalyzed highly chemo- and regioselective C-H bond functionalization of phenols with haloalkynes - Adak, Tapas; Schulmeister, Jürgen; Dietl, Martin C.; Rudolph, Matthias; Rominger, Frank; Hashmi, A. Stephen K. (European journal of organic chemistry, 2019)
A highly chemo- and stereoselective addition of unprotected phenols to haloalkynes was developed. A ligand and counterion controlled process enabled the highly site-selective and chemoselective C-H bond functionalization of phenol derivatives with haloalkynes in moderate to excellent yield at room temperature. The simple availability of the starting materials in combination with the preferred para-C-H functionalization over a competing O-H insertion makes this an attractive protocol. The stereoselectivity of the products depends on the choice of the catalyst. From a synthetic prospective, this method offers an efficient route towards vinyl chlorides, which are valuable precursors for the synthesis of pharmaceutical drugs.